When find the derivative, we are going to lower the power by 1, that is
2/3-1=2/3-3/3=(2-3)/3=-1/3
If g (x)= x 2/3 then g (x)= 2 over 3 (2/3) x -1/3
OK OK I get it. (How to solve by using the power rule.)
What I don't get is how do you reduce 2/3 by 1 to get -1/3.
I know this sounds kinda stupid, but can somebody please break this down step by step on how to reduce this fraction by 1 before I go crazy!
ok,
you have to solve 2/3-1.
to do that you have to have 2 frations having the same bottom, so you have to write 1 as a fraction.
Since 1=3/3, you have to do know 2/3-3/3
to substract 2 fractions with the same bottom, you substract the tops and copy the bottom, thus -1/3, since 2-3=-1, and the common bottom is 3